MODERN DISCOURSE OF CIVIL SERVICE IN RUSSIA: A VIEW THROUGH THE PRISM OF ADMINISTRATIVE PARADIGMS - Борщевский, Георгий (Public Administration Issues, 2022)
In this article we examine the features of the current stage of Russian civil service development through the prism of the basic administrative paradigms – Weberian rational bureaucracy, New Public Management (NPM) and Good Governance; and we identify the prevailing paradigms in scientific discourse, electoral political discourse and modern legal discourse. We use such research methods as follows: content analysis, thesaurus analysis, bibliometric analysis of publications, comparative legal analysis. We propose some criteria for identifying administrative paradigms using a set of thesaurus words, as well as methodological tools for comparing with paradigms: a) scientific articles on state bureaucracy, b) election programs of Russian political parties in terms of reforming the civil service, c) regulatory documents containing the goals of the current stage of the Russian civil service development. As a result of the study, we have found that the Weberian paradigm dominates in scientific publications on law, NPM paradigm – on management and economics, Good Governance paradigm – on sociology and political science, which indicates the multiparadigmality of modern research. During the 2016 and 2021 parliamentary election campaigns, political parties of the entire ideological spectrum worked out a request for social justice, which was due to the predominance of theses in their programs corresponding to Good Governance. Regulation of the Russian civil service development in the period is carried out at the intersection of managerial and Weberian models. The first is manifested in the rigid formalization of the civil servants’ activities, and the second – in attempts to make the bureaucracy efficient, compact and complaisant. The preservation of the civil service’ closeness is confirmed by a decrease in the share of program measures equivalent to Good Governance, which contradicts the attitude towards openness and justice, fixed in scientific and political discourse.